A Comprehensive Review of Maple Sap Microbiota and Its Effect on Maple Syrup Quality. Issue 6 (18th August 2022) - Jennifer J., Perry; Maria C., Fiore
ABSTRACT: When in the tree xylem, maple sap is void of microbial contaminants, including bacteria, yeast, and molds. Once tapped, however, the liquid which is comprised primarily of water, becomes a nutrient reservoir for environmental microbiota. Introduction of microorganisms is exacerbated by poor sanitation practices, sap storage procedures, as well as environmental factors. Excessive microflora growth degrades the quality of maple sap, resulting in lower quality maple syrup. This review will discuss the documented microflora of sap and sources of introduction, processing practices which augment risk of contamination, the various sap and syrup defects associated with microbial growth, as well as the resulting microflora of finished syrup.